Characteristics of Organizational Culture on the Quality of Health Services in Meepago Region (Nabire Regency) Study in the Field of Public Administration - Tebay, Vince; Ratang, Westim (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to emphasizes the characteristics of organizational culture and its impact on the quality of health services in public administration in Nabire Regency. The main argument in this research places Robbins' idea of ​​organizational culture into the characteristics of primary organizational culture. Method used in this research is descriptive qualitative, with the data source from observations, in-depth interviews, and documentation. The findings in this research showed that secondary organizational cultural characteristics also had a dominant influence in shaping organizational culture at the research location. The findings in this research show that primary cultural characteristics alone are not enough to achieve optimal quality of health services, especially in conditions in countries or regions that have not yet been settled and established, but on this occasion I dared to add new organizational cultural characteristics which I call cultural characteristics. Further research can develop the results of this research to investigate health services with a wider scope or in different cases in other places.